A wavelet based method for electrical stimulation artifacts removal in electromyogram. (September 2015) - Yochum, Maxime; Binczak, Stéphane
Abstract: A technique for artifact removal based on the continuous wavelet transform is presented. It uses common mother wavelets to find the temporal localization of stimulation artifacts on electromyogram signal recording during an electrical surface evoked contraction of a muscle. This method is applied with different kinds of stimulation pulse parameters including shape and duration changes. This method is used with standard stimulation pulse waveforms such as monophasic or biphasic ones. It can also be applied when the artifacts and M waves are in the same range of amplitude where threshold techniques are inefficient. Lastly, a method to determine which mother wavelet efficiently removed artifacts is proposed, results indicate the Haar wavelet performs best among fourteen tested wavelets.